2012
DOI: 10.1590/s0104-92242012000100002
|View full text |Cite
|
Sign up to set email alerts
|

Friction Stir Welding of very thin plates

Abstract: ResumoOs resultados obtidos no presente estudo, referentes a friction stir welding de chapas de alumínio, cobre, cobre-zinco

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, the tensile specimen fractured at the nugget zone (NZ) due to the irregular thickness rather than the existence of defects. Galvao et al [30] performed µ-FSW of 1 mm-thick sheets of aluminum, copper, copper-zinc, and zinc alloys, and found that the increase in welding speed enhanced process productivity and raised the degree of grain refinement, improving mechanical properties. Panchal, M. et al [31] successfully connected ultrathin (0.5 mm-thick) commercial Al using µ-FSW technology.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tensile specimen fractured at the nugget zone (NZ) due to the irregular thickness rather than the existence of defects. Galvao et al [30] performed µ-FSW of 1 mm-thick sheets of aluminum, copper, copper-zinc, and zinc alloys, and found that the increase in welding speed enhanced process productivity and raised the degree of grain refinement, improving mechanical properties. Panchal, M. et al [31] successfully connected ultrathin (0.5 mm-thick) commercial Al using µ-FSW technology.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the process characteristics and mode of heat generation, welds are composed of two main areas which are referred to as the thermo-mechanically affected zone (TMAZ) and the heat-affected zone (HAZ) [13]. In the HAZ, the temperatures reached affect material microstructure and mechanical properties without plastic deformation, whereas in the TMAZ, material deforms plastically by the high temperature produced by the welding tool [14]. In the TMAZ there are two additional areas, one with elongated grains, deformed in the tool rotation direction, and another one with a fully recrystallized microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [5][6][7], [10,11], [14][15][16][17][18] were performed on the thermal and mechanical effects produced during FSW. These effects are mainly due to the asymmetry of the flow around the material, caused by the difference in the relative velocity between the two sides of the weld.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by severe plastic deformation and elongation of the base material grains as well as exposure to elevated temperature because of the proximity to the WN. In the heat-affected zone (HAZ) which is common to all welding processes, the material experiences thermal conditions that modify its microstructure and/or the mechanical properties without any plastic deformation [16]. Peel et al 2003 [7] studied the microstructure, the mechanical properties and the residual stresses as a function of the welding speed in AA5083 Friction Stir Welds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation